Leaf architecture of Eugenia L. (Myrtaceae) on the Algodoal, Maiandeua peninsula, Pará - Alvarez, Adalgisa da Silva; Potiguara, Raimunda Conceição de Vilhena; Santos, João Ubiratan Moreira dos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
A study was carried out on the pattern of leaf-blade venation of six species of Eugenia L. (Myrtaceae), that occur in Algodoal, Maiandeua, Pará. All species which were found have brochidodromous venation. Although the species could not be separated on the basis of leaf venation pattern, however differences in anatomical characters were discovered that allowed the construction of an identification key to the species.
Keywords: Venation; Eugenia; Leaf anatomy